IDENTIFICATION OF VIBRIOSIS FROM SEAWEED CULTURE IN LOMBOK, WEST NUSA TENGGARA - Dewi Nur'aeni Setyowati; Nunik Cokrowati (Journal of Fish Health, 2021)
The aim of the study was to identify vibrio disease in Eucheuma cottonii samples which had the characteristics of ice-ice disease, namely the thallus was whitish and broken. The research was conducted at two locations in Lombok, namely in Ekas Bay and in the waters of Buwun Mas Village. The samples were identified as vibrio bacteria at the Sekotong Marine Aquaculture Center using biochemical methods. The results showed that vibrio bacteria were associated with ice-ice disease in the observed seaweeds. The types of vibrio bacteria that cause ice-ice disease in samples in Ekas Bay and Buwun Mas are Vibrio parahaemolyticus, Vibrio alginolyticus, and Vibrio damsela.